(untitled) (mathematica didactica, 2003)
Dynamic geometry systems are powerful tools for the geometric modelling of two-dimensionally interpretable parts of reality which surrounds us. A modelling task involves the reconstruction of the geometry which has been consciously or subconsciously created in our world by "human hand" or which can be found in the natural environment. The result of a corresponding reconstruction process is a static or dynamic model. Reconstructive modelling provides us with more possibilities than the traditional modelling in the geometry classroom. This new computer supported modelling method induces open learning environments through students’ self-selection and solving of authentic examples. These environments are conducive to project work.